(untitled) (Journal of Environmental Science and Natural Resources, 2016)
A study was conducted to assess the adequacy, utilization and repayment of Grameen Bank (GB) income generating loans on rural women in selected areas of Tangail district. The study was conducted with socio-economic characteristics of the women borrowers, assessing the adequacy, utilization and repayment of loan. With this end in view, 60 respondents were purposively selected from three villages namely Hemnagar, Volapara and Shimlapara of which 10 were engaged in farming, 21 were engaged in livestock rearing, 19 were engaged in petty business, 5 were engaged in tailoring and 5 were indirectly engaged in van/rickshaw pulling. Tabular and statistical analyses were applied for achieving the objectives. In the study area, higher proportions (55 per cent) of women were middle aged and 93 percent were married. About 75 percent had signature ability, 18 and 7 per cent studied up to primary and secondary level respectively. Average family size of the respondents was5.36; average annual income and saving of the respondents were Tk. 65958.05 and 8769.65 respectively. Six explanatory variables i.e. Age, education, family size, occupation, income and expenditure were considered for repayment of loan in empirical model. Age, family size, income and expenditure had significant impact on repayment of loan. Average amount of credit received by the respondents was Tk. 8139 and on an average 82 percent of the loaned money was utilized for the reported IGAs. Due to poor economic condition, the respondents could not utilize the total loaned money in productive purposes. Overall loan recovery percentage was found to be quite satisfactory. They repaid their loan on time with the hope of getting more credit in future and because of regular supervision by the banks field level workers and pressure of the group leaders. J. Environ. Sci. & Natural Resources, 8(2): 131-134 2015